CDK7 inhibition augments response to multidrug chemotherapy in pancreatic cancer - Zeng, Siyuan; Lan, Bin; Ren, Xiaofan; Zhang, Shuman; Schreyer, Daniel; Eckstein, Markus; Yang, Hai; Britzen-Laurent, Nathalie; Dahl, Andreas; Mukhopadhyay, Debabrata; Chang, David; Kutschick, Isabella; et al. (Journal of Experimental & Clinical Cancer Research, 2022)
Background: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive cancer with a dismal prognosis. Although combined treatment with gemcitabine and albumin-bound paclitaxel has improved the prognosis of PDAC, both intrinsic and acquired chemoresistance remain as severe hurtles towards improved prognosis. Thus, new therapeutic targets and innovative strategies are urgently needed. Methods: In this study, we used the KPC mouse model-derived PDAC cell line TB32047 to perform kinome-wide CRISPR-Cas9 loss-of-function screening. Next-generation sequencing and MAGeCK-VISPR analysis were performed to identify candidate genes. We then conducted cell viability, clonogenic, and apoptosis assays and evaluated the synergistic therapeutic effects of cyclin-dependent kinase 7 (CDK7) depletion or inhibition with gemcitabine (GEM) and paclitaxel (PTX) in a murine orthotopic pancreatic cancer model. For mechanistic studies, we performed genome enrichment analysis (GSEA) and Western blotting to identify and verify the pathways that render PDAC sensitive to GEM/PTX therapy. Results: We identified several cell cycle checkpoint kinases and DNA damage-related kinases as targets for overcoming chemoresistance. Among them, CDK7 ranked highly in both screenings. We demonstrated that both gene knockout and pharmacological inhibition of CDK7 by THZ1 result in cell cycle arrest, apoptosis induction, and DNA damage at least predominantly through the STAT3-MCL1-CHK1 axis. Furthermore, THZ1 synergized with GEM and PTX in vitro and in vivo, resulting in enhanced antitumor effects. Conclusions: Our findings support the application of CRISPR-Cas9 screening in identifying novel therapeutic targets and suggest new strategies for overcoming chemoresistance in pancreatic cancer.
CRIS-Team Scopus Importer:2022-08-19
Keywords: CDK7; CRISPR-Cas9; FOLFIRINOX; Gemcitabine; Paclitaxel; THZ1

Chemoresistance in Pancreatic Cancer - Zeng, Siyuan; Pöttler, Marina; Lan, Bin; Grützmann, Robert; Pilarsky, Christian; Yang, Hai (International Journal of Molecular Sciences, 2019)
Pancreatic ductal adenocarcinoma (PDAC), generally known as pancreatic cancer (PC), ranks the fourth leading cause of cancer-related deaths in the western world. While the incidence of pancreatic cancer is displaying a rising tendency every year, the mortality rate has not decreased significantly because of late diagnosis, early metastasis, and limited reaction to chemotherapy or radiotherapy. Adjuvant chemotherapy after surgical resection is typically the preferred option to treat early pancreatic cancer. Although 5-fluorouracil/leucovorin with irinotecan and oxaliplatin (FOLFIRINOX) and gemcitabine/nab-paclitaxel can profoundly improve the prognosis of advanced pancreatic cancer, the development of chemoresistance still leads to poor clinical outcomes. Chemoresistance is multifactorial as a result of the interaction among pancreatic cancer cells, cancer stem cells, and the tumor microenvironment. Nevertheless, more pancreatic cancer patients will benefit from precision treatment and targeted drugs. Therefore, we outline new perspectives for enhancing the efficacy of gemcitabine after reviewing the related factors of gemcitabine metabolism, mechanism of action, and chemoresistance.
CRIS-Team Scopus Importer:2019-09-20
Keywords: chemoresistance; FOLFIRINOX; gemcitabine; pancreatic cancer; PDAC

CRISPR-Cas9 Screen Identifies DYRK1A as a Target for Radiotherapy Sensitization in Pancreatic Cancer - Lan, Bin; Zeng, Siyuan; Zhang, Shuman; Ren, Xiaofan; Xing, Yuming; Kutschick, Isabella; Pfeffer, Sina; Frey, Benjamin; Britzen-Laurent, Nathalie; Grützmann, Robert; Cordes, Nils; Pilarsky, Christian (Cancers, 2022)
Although radiation therapy has recently made great advances in cancer treatment, the majority of patients diagnosed with pancreatic cancer (PC) cannot achieve satisfactory outcomes due to intrinsic and acquired radioresistance. Identifying the molecular mechanisms that impair the efficacy of radiotherapy and targeting these pathways are essential to improve the radiation response of PC patients. Our goal is to identify sensitive targets for pancreatic cancer radiotherapy (RT) using the kinome-wide CRISPR-Cas9 loss-of-function screen and enhance the therapeutic effect through the development and application of targeted inhibitors combined with radiotherapy. We transduced pancreatic cancer cells with a protein kinase library; 2D and 3D library cells were irradiated daily with a single dose of up to 2 Gy for 4 weeks for a total of 40 Gy using an X-ray generator. Sufficient DNA was collected for next-generation deep sequencing to identify candidate genes. In this study, we identified several cell cycle checkpoint kinases and DNA damage related kinases in 2D-and 3D-cultivated cells, including DYRK1A, whose loss of function sensitizes cells to radiotherapy. Additionally, we demonstrated that the harmine-targeted suppression of DYRK1A used in conjunction with radiotherapy increases DNA double-strand breaks (DSBs) and impairs homologous repair (HR), resulting in more cancer cell death. Our results support the use of CRISPR-Cas9 screening to identify new therapeutic targets, develop radiosensitizers, and provide novel strategies for overcoming the tolerance of pancreatic cancer to radiotherapy.
CRIS-Team Scopus Importer:2022-01-14
Keywords: CRISPR-Cas9; DNA damage repair; DNA double-strand break; DYRK1A; Harmine; Pancreatic cancer; Radioresistance; Radiotherapy

The Role of Exosomes in Pancreatic Cancer - Lan, Bin; Zeng, Siyuan; Grützmann, Robert; Pilarsky, Christian (International Journal of Molecular Sciences, 2019)
Pancreatic cancer remains one of the deadliest cancers in the world, as a consequence of late diagnosis, early metastasis and limited response to chemotherapy, under which conditions the potential mechanism of pancreatic cancer progression requires further study. Exosomes are membrane vesicles which are important in the progression, metastasis and chemoresistance in pancreatic cancer. Additionally, they have been verified to be potential as biomarkers, targets and drug carriers for pancreatic cancer treatment. Thus, studying the role of exosomes in pancreatic cancer is significant. This paper focuses on the role of exosomes in the proliferation, metastasis and chemoresistance, as well as their potential applications for pancreatic cancer.
CRIS-Team Scopus Importer:2019-09-17
Keywords: biomarker; chemoresistance; exosomes; pancreatic cancer